DAMPAK INOVASI DAN PEMANFAATAN MEDIA SOSIAL TERHADAP KINERJA UMKM KOPI TOLAKI DI DESA TRIDANA MULYA KECAMATAN LANDONO KABUPATEN KONAWE SELATAN - Nurpadila Nurpadila; Iskandar Zainudin Rela; Megafirmawanti Lasinta; Dian Agustin (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2024)
This study aims to ascertain the role of innovation and the utilisation of social media, and its impact on the performance of Tolaki Coffee MSMEs in Tridana Mulya Village. The informants for this study were selected using the purposive method, with the inclusion criteria being that the informants must be owners and employees of the aforementioned MSMEs. This resulted in a total of six informants being included in the study. This research employs a qualitative methodology. Data were collected through observation, in-depth interviews, and document analysis with the assistance of an interview guide. The research will concentrate on the function of innovation, the role of social media, and the performance of MSMEs. The data analysis employs a descriptive qualitative approach, with reference to the Miles & Huberman model. This includes the processes of data reduction, data presentation, and conclusion drawing or data verification. The findings indicate that the innovations implemented in Tolaki Coffee MSMEs possess competitive advantages, facilitate business growth, enable adaptation to changes, such as conducting market and industry research to comprehend the latest technological developments in the coffee industry, and enhance customer satisfaction. The use of social media to enhance the performance of MSMEs can be observed in the context of products, promotional activities, locations, and pricing. The function of innovation in improving the performance and productivity of coffee MSMEs is to offer distinctive product features, such as the introduction of new flavor variants, innovative serving methods, or appealing packaging, with the objective of attracting new customers. Concurrently, the role of social media is to increase product visibility and sales by leveraging social media platforms that align with the characteristics of the target market.